PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM - Rusydina, Arifah; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTIn conducting investment, investors are faced by the uncertainty between the return which will be gained and the risk which will be faced by the company. This research is meant to find out the influence of liquidity, solvability, activity, profitability and market ratio to the stock return. Population is all companies in LQ45 index which are listed in Indonesia Stock Exchange. The sample collection technique has been done by using purposive sampling and multiple regressions analysis technique. The result of the test shows that simultaneously current ratio, debt to equity ratio, total asset turnover, return on equity and earning per share has influence to the stock return. This result is supported by the acquisition of correlation coefficient level is 61.4% shows the correlation among the models which have been used in this research to the return is firm. The result of partial test shows that current ratio, and total asset turnover does not give any significant influence to the stock return. Meanwhile, debt to equity ratio, return on equity and earning per share shows significant influence to the stock return.Keywords: Current Ratio, Debt To Equity Ratio, Total Asset Turn Over, Return On Equity, Return Saham